The CILLO-E Hypothesis: Erythrocyte-Driven Acidosis and Early Eryptosis as Drivers of Cancer-Associated Anemia - Aydın, Hüseyin (Frontiers in Oncology, 2025)
BackgroundThe tumor microenvironment (TME) is characterized by high lactate and proton accumulation resulting from glycolytic metabolism. While acidosis is known to influence immune and stromal cells, its direct effects on erythrocytes—the most abundant circulating cells—remain underexplored.MethodsAn integrative review of cancer metabolism, erythrocyte physiology, and lactate transport systems was conducted using PubMed and Web of Science. From this synthesis, the CILLO-E hypothesis (Cancer-Induced Lactate Load on Erythrocytes) was formulated.ResultsThe hypothesis proposes that lactate and protons enter erythrocytes via MCT1, leading to intracellular acidification. This process disrupts glycolytic enzymes, reduces ATP production, and impairs Na+/K+-ATPase and Ca²+-ATPase activity. Energy depletion causes Ca²+ overload, which activates scramblase and inhibits flippase, resulting in PS exposure and premature eryptosis. In parallel, reduced 2,3-BPG synthesis alters hemoglobin–oxygen affinity, exacerbating hypoxia. Together, these mechanisms provide a biochemical explanation for the normocytic–normochromic anemia frequently observed in cancer. Importantly, cancer-associated anemia is multifactorial, and CILLO-E should be viewed not as a comprehensive explanation but as a complementary mechanism acting through lactate-induced erythrocyte dysfunction.ConclusionsThe CILLO-E hypothesis reframes erythrocytes as active metabolic targets in the TME rather than passive oxygen carriers. By linking lactate-driven metabolic stress to erythrocyte dysfunction, anemia, and systemic hypoxia, it suggests a feedback loop that promotes tumor progression and highlights opportunities for erythrocyte-based biomarkers and therapeutic strategies.